Efficiency of an Online Class in terms of Academic Performance of Grade 12 HUMSS Students at Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The mode of learning transitioned from face-to-face to blended learning. Every student has learning preferences that help them have smooth retention and comprehension. Some formulated theories about learning style, including the VARK models and Dunn and Dunn Learning Style, which is the most extensively used and understood. We must limit our investigation to one or two models to prevent a complicated study. It seemed to mirror the students' and teachers' experiences. The study is concerned with the phenomenology of students and teachers, as well as communicating and transferring knowledge from one to another, and the effects of distance learning would be more compromising and understandable to know these complex issues concerning students' academic performance and learning styles.  This study used descriptive research design, a data collection that uses one or more appropriate methods such as observations, interviews and surveys. It is aimed to formulate a hypothesis and to determine and describe the impact of learning style on the academic performance of grade twelve HUMSS students at Bestlink College of the Philippines. Simple random sampling was used to select the students that will serve as respondents. Surveys and online questionnaires were used as research instruments for data collection. One of the primary purposes of this study is to examine the impacts of learning styles on the academic performance of Grade 12 HUMSS students at Bestlink College of the Philippines. Earlier research studies show that students' learning styles impact their academic performance in different types. Furthermore, they also experience and encounter different factors affecting their learning style and academic performance.
Keywords: Pandemic; Learning Styles; Academic Performance; Mode of Learning; HUMSS Students